Evaluación de dos crioprotectores (Etilenglicol y propilenglicol) en la conservación lenta de ovocitos en cobayos (cavia porcellus) en el laboratorio de la carrera de medicina veterinaria - Villamarín Álvarez, Kimberley Katiuska (2016)
This research was done in the laboratory of biotechnology of the reproduction of the Technique University of Cotopaxi . The Oocytes in study had extracted of 30 females guinea pigs of 2nd childbirth, the same that were sacrificed and of which had a total of 420 oocytes cryopreservation , these oocytes were collected in sterile containers with doubly distilled water for fresh maintenance of ovaries, avoiding cause damage to the structures. The purpose of this study was the evaluation of two cryoprotectants (ethylene glycol and propylene glycol) for the conservation slow of oocytes from Guinea pig (cavia porcellus)....